Dialectics of Policy Instruments and the Effectiveness of Educational Governance: A Conceptual Synthesis in a Contemporary Perspective - Hasanudin; Lanlan Muhria; Dhike Noordestiasari Hanurajasa (PT. Caesarindo Triloka Persada, 2026)
Educational policy formulation in the digital era requires the precise selection of strategic instruments to ensure the effectiveness of institutional governance. This study aims to synthesize various theoretical perspectives on policy instrument typologies and evaluate their implications for contemporary educational management transformation. The method employed is a narrative literature review analyzing academic documents from reputable databases over the last ten years. Findings indicate that reliance on mandate-based regulatory instruments tends to create administrative rigidity that stifles pedagogical innovation. The integration of a policy mix that includes incentives and internal capacity-building is more effective at building organizational resilience. This article makes a theoretical contribution by offering a conceptual framework for adaptive governance responsive to the dynamics of the educational ecosystem.